2009
DOI: 10.1007/s00011-009-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

The RBL-2H3 cell line: its provenance and suitability as a model for the mast cell

Abstract: The RBL-2H3 cell line is a commonly used histamine-releasing cell line used in inflammation, allergy and immunological research. Quite commonly, it is referred to in research papers as a mast cell line, despite the fact that it is derived from basophils. There is also a lack of consistency, both between different research groups using the same cell line and with both mast cell and basophil physiology. The review follows the development of the RBL-2H3 cell line from its inception and then goes on to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
152
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(160 citation statements)
references
References 79 publications
0
152
0
3
Order By: Relevance
“…Assay for ␤-Hexosaminidase-The release of a preformed granular enzyme, ␤-hexosaminidase, in mast cells correlates well with histamine release (15). Finally, 40 l of each supernatant was transferred to a fresh 96-well plate and mixed with 50 l of substrate solution (5 mm 4-nitrophenyl N-acetyl-␤-D-glucosaminide in 50 mM citric acid buffer, pH 4.5).…”
Section: Counts Of Mast Cells and Eosinophils In The Intestinalmentioning
confidence: 99%
“…Assay for ␤-Hexosaminidase-The release of a preformed granular enzyme, ␤-hexosaminidase, in mast cells correlates well with histamine release (15). Finally, 40 l of each supernatant was transferred to a fresh 96-well plate and mixed with 50 l of substrate solution (5 mm 4-nitrophenyl N-acetyl-␤-D-glucosaminide in 50 mM citric acid buffer, pH 4.5).…”
Section: Counts Of Mast Cells and Eosinophils In The Intestinalmentioning
confidence: 99%
“…The present article describes the biological effects of fruiting body extracts from the T. populinum mushroom on the degranulation of RBL-2H3 cells. RBL-2H3 is a tumorigenic rat basophilic cell line [10], which is widely used for investigations on degranulation and its mechanistic aspects [11][12][13][14][15][16][17]. Furthermore, the influence on IL-2 release of Jurkat T cells, IL-8 release from mast cell line HMC-1, and cytotoxicity were tested.…”
Section: Introductionmentioning
confidence: 99%
“…P. Diniz et al found that the stimulatory effect of PEMF with the 15 Hz pulse burst and 7 mTesla on bone-tissue-like formations was associated with the increase in the number of cells and the enhancement of the cellular differentiation [6]. Most researchers had reported the positive efficacy of exposure to electromagnetic fields on basic cellular functions such as control of cell proliferation, protein synthesis, gene transcription and expression, ion transport, ligand-receptor binding events, neurite outgrowth, and protein kinase activation, among others [7].…”
Section: Introductionmentioning
confidence: 99%